The Deceased in el-Salamuni Necropolis: Following Osiris in Classical Dress - Omran, Wahid (Mitteilungen des Deutschen Archäologischen Instituts Kairo, 2024)
This article investigates the depiction of the deceased in unpublished Graeco-Roman tombs of el-Salamuni, the main necropolis of Akhmim, ancient Panopolis, during the Graeco-Roman Period, where the male/female deceased is often represented at a large scale dressed in a daily, luxurious classical-style garment, displaying a kind of greatness, power, and wealth. The deceased also often hold a special attribute-object in their hands, containing the rotulus and the situla of Isis. During the author’s investigation of the Graeco-Roman tombs, the large classical depiction of the patron of the tomb was found to be a special characteristic that is extensively depicted in the el-Salamuni necropolis, either in the antechamber or the burial chambers of the tombs. The paper visualises and analyses the religious and artistic reasons for this special iconography.